THE SEMANTICS OF INNOVATIONS IN THE EDUCATIONAL ENVIRONMENT: ANALYSIS OF PERCEPTIONS, ATTITUDES, AND IMPLEMENTATION MODELS - Kwilinski, Aleksy; Vakhovych , Iryna (Socio-economic relations in the digital society, 2025)
The article presents a comprehensive analysis of university faculty and students’ perceptions of educational innovations implemented within the context of national education system transformation. It has been established that the perception of innovations is influenced by a broad range of socio-psychological, conceptual-methodological, and systemic factors which together form an unfavourable innovation climate in Ukrainian educational environments. Key barriers to innovation implementation are identified, including systemic instability, resource deficits, managerial disintegration, lack of strategic vision, low awareness among educational participants, insufficient motivational readiness for change, and a dominant instrumental approach to innovations. The article describes the semantic structures of both positive and negative perceptions of innovation, which significantly affect the dynamics of innovation processes. Positive attitudes are shown to be based on perceptions of appropriateness, safety, modernity, transparency, and the democratic nature of innovations, while negative attitudes emerge in conditions of unpredictability, authoritarianism, inadequate resource support, and the perception of innovations as externally imposed. A five-step technological model of innovation implementation is proposed, including awareness-raising, involvement, feedback and adjustment, resistance management, and outcome evaluation. The use of integrated information, psychotechnological, and interventional methods is substantiated as an effective strategy for shaping a positive image of innovations, activating participation in innovation processes, and ensuring their successful realization. The findings are significant for the development of innovation management strategies in educational settings, particularly in terms of fostering motivational readiness for change and enhancing the overall innovative capacity of Ukraine’s educational system.